HASIL BELAJAR PENDIDIKAN AGAMA ISLAM MENGGUNAKAN APLIKASI QUIZIZZ DI UPTD SMPN 4 KECAMATAN LAREH SAGO HALABAN - Filtra Yeni; Zulfani Sesmiarni; Rodi Rodi; Mutammimul Hayati (CV. ADIBA AISHA AMIRA, 2024)
Engaging and enjoyable learning is a condition that students aspire to. When students are enthusiastic and highly motivated in their learning, their academic performance will improve. To achieve engaging learning, various media can be used, one of which is the Quizizz application, a medium for learning while playing. This research aims to describe the improvement in Islamic Religious Education learning outcomes using the Quizizz application in class IX.2 UPTD SMPN 4 Lareh Sago Halaban District. The approach that will be used in this research is classroom action research (CAR) with pre-cycle, cycle 1, cycle 2, and cycle 3. The type of research used in this study is descriptive quantitative. The research results indicate that the students' learning completeness at the initial condition before using the Quizizz application was 31%. After using the Quizizz application in the pre-cycle, the percentage of students' learning outcomes reached 42%, in Cycle I it increased to 54%, in Cycle II it increased to 65%, and in Cycle III it increased to 81%. Based on the results of the classroom action research that has been conducted, it can be concluded that the application of the Quizizz application as an assessment medium in Islamic Religious Education and Character Education subjects effectively improves students' learning outcomes. The increase in the percentage of learning completeness from 42% in the pre-cycle to 81% in Cycle III indicates that the use of the Quizizz application can be an interesting alternative to enhance students' learning outcomes.